The Legal Implications of Breast Milk Donation on Nasab Status: Yusuf Qardhawi’s Perspective - Salsabila, Tsaniatus; Hamidah, Tutik; Anam, Khoirul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
This study examines the practice of breast milk donation in a village and its impact on nasab (lineage) status from Yusuf Qaradawi's perspective on breastfeeding regulations. The research aims to analyze how this practice influences mahram relationships in the village community. A qualitative approach with a case study method was used, employing in-depth interviews and documentation. The findings show that 19 residents have participated in breast milk donation. Among them, 10 individuals are considered mahram according to Yusuf Qaradawi’s criteria, having been breastfed more than five times, while eight individuals are not mahram as they were only breastfed once. A unique case was found where a couple unknowingly married their milk sibling, leading to their children performing tajdidunnikah (marriage renewal). The village community believes that a single instance of breastfeeding establishes a mahram relationship, differing from Yusuf Qaradawi’s view. The novelty of this research lies in its analysis of real cases within the context of Islamic family law and its application in rural society. This study contributes to the development of Islamic legal understanding regarding breast milk donation and provides a sociological perspective through Emile Durkheim's Structural Functionalism theory, demonstrating that mechanical solidarity plays a role in shaping legal norms in society.